2022
DOI: 10.1038/s41593-021-00999-y
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale deep multi-layer analysis of Alzheimer’s disease brain reveals strong proteomic disease-related changes not observed at the RNA level

Abstract: The biological processes that are disrupted in the Alzheimer’s disease (AD) brain remain incompletely understood. In this study, we analyzed the proteomes of more than 1,000 brain tissues to reveal new AD-related protein co-expression modules that were highly preserved across cohorts and brain regions. Nearly half of the protein co-expression modules, including modules significantly altered in AD, were not observed in RNA networks from the same cohorts and brain regions, highlighting the proteopathic nature of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
642
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(700 citation statements)
references
References 81 publications
55
642
3
Order By: Relevance
“…Here, we see evidence of a direct relationship between Pyk2 and MAPK1 activity, raising the possibility that Pyk2-mediated activation of MAPK1 may also lead to decreased Tau phosphorylation in PS19 0/+ animals. MAPKs, a family of kinases that also include JNK, have long been implicated in the pathogenesis of AD [ 77 – 80 ], and a recent large-scale proteomic analysis of postmortem AD brain tissue from the Accelerated Medicines Partnership for Alzheimer’s Disease (AMP-AD) Consortium revealed significant enrichment for proteins related to MAPK signaling and metabolism that strongly correlated with cognitive decline [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we see evidence of a direct relationship between Pyk2 and MAPK1 activity, raising the possibility that Pyk2-mediated activation of MAPK1 may also lead to decreased Tau phosphorylation in PS19 0/+ animals. MAPKs, a family of kinases that also include JNK, have long been implicated in the pathogenesis of AD [ 77 – 80 ], and a recent large-scale proteomic analysis of postmortem AD brain tissue from the Accelerated Medicines Partnership for Alzheimer’s Disease (AMP-AD) Consortium revealed significant enrichment for proteins related to MAPK signaling and metabolism that strongly correlated with cognitive decline [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…When considering the products of the 196 genes assessed, 66 proteins with significant positive correlations between protein abundance and MMSE (mini-mental state exam) (p < 0.05; higher abundance correlated with better cognition) (Table S6) were identified in the ROSMAP and Banner (Banner Sun Health Research Institute) populations (Johnson et al, 2022). Johnson et al reported that modules “post-synaptic density” and “protein transport” were enriched in proteins correlated with resilience that were previously identified in another study (Johnson et al, 2022). In an analysis that directly compared protein abundance in AD vs AsymAD (individuals with AD pathology and without significant cognitive impairment) (Supplementary Table 2 in Johnson et al), 1,540 proteins had higher abundance in AsymAD (log2FC > 0 with adj.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to identify proteins that shared resilience signatures in the human ROSMAP and Banner data set, data from Johnson et al (Johnson et al, 2022) was used (Supplementary Table 6, considering p- and bicor values for MMSE30). Proteins that were upregulated in AsymAD vs AD can be found in Supplementary Table S2 of that publication.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, while the ROS/MAP dataset presented an opportunity to study the effects of rs16969968 on a background of an unusually-low smoking prevalence (Cornelius et al, 2022), future work would benefit from inclusion of a more diverse group of subjects with more robust assessment of smoking history. In terms of approaches, RNA sequencing data has been previously found to not fully capture the protein-level changes in AD brains, which were detectable through a proteomic analysis (Johnson et al, 2022). This limitation should be considered when interpreting the findings of our study, in which we utilized bulk and single-nucleus RNAseq from the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%